2022
DOI: 10.1186/s43163-022-00290-2
|View full text |Cite
|
Sign up to set email alerts
|

Audiovestibular and vaccination complications of COVID-19

Abstract: Objectives Since its first appearance in Wuhan December 2019, SARS-CoV2 virus received great attention due to its severe symptoms and high spread causing COVID-19 disease which spread all over the world like a pandemic. The causative virus is capable of human-to-human transmission via droplet and direct contact suggesting that upper respiratory tract is the main site to virus manifestations. There is a great diversity in its clinical picture, although the severe respiratory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…While other published literature were in line with our hearing loss findings [20,21,22], we are the first to confirm an increased incidence of tinnitus and vertigo post COVID-19 vaccines. [23,24] Although the pathophysiology of audiovestibular events following vaccination is unclear, proposed mechanisms include an immune mediated injury due to exaggerated cytokine responses leading to vasculitic events, antibody cross-reactivity and molecular mimicry [2]. Another suggested mechanism is that mRNA vaccines can cause reactivation of previous latent viruses resulting in sudden hearing loss [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While other published literature were in line with our hearing loss findings [20,21,22], we are the first to confirm an increased incidence of tinnitus and vertigo post COVID-19 vaccines. [23,24] Although the pathophysiology of audiovestibular events following vaccination is unclear, proposed mechanisms include an immune mediated injury due to exaggerated cytokine responses leading to vasculitic events, antibody cross-reactivity and molecular mimicry [2]. Another suggested mechanism is that mRNA vaccines can cause reactivation of previous latent viruses resulting in sudden hearing loss [25].…”
Section: Discussionmentioning
confidence: 99%
“…Following the implementation of COVID 19 vaccines commencing in December 2020[1], concerns have been raised globally about a possible association between COVID-19 vaccinations and audiovestibular conditions [2]. Australia's COVID-19 vaccination rollout commenced on 22 February 2021 [3].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2, the infectious agent for the ongoing COVID-19 pandemic, often has long-term impacts on the health of individuals who survive initial infection [1][2][3][4][5][6] and can lead to premature death [1]. Multiple organ systems may be singly or interactively impacted by the daily living (ADL), and reduced quality of life (QOL) [6,10] gustatory and gastrointestinal impacts [4] neural system invasion through the neuro/olfactory bulb linkage [5,6] and/or through the angiotensin-converting enzyme 2 mechanism found in alveoli, glial cells, and neurons [4] sensory loss (most commonly taste and smell, but also hearing; [2,4] neurological impairments and multiorgan failure [4,5] cognitive processing difficulties sometimes referred to as "brain fog" [3,6], and inner-ear-related conditions such as dizziness, vertigo, and tinnitus [2,4,16]. No universal upper length of chronicity limit has been established, though an upper limit of one year is sometimes noted [3,17].…”
Section: Introductionmentioning
confidence: 99%
“…
SARS-CoV-2, the infectious agent causing the ongoing COVID-19 pandemic, often has long-term impacts on the health of those who survive initial infection [1][2][3][4][5][6] and can lead to premature death [1]. An understudied outcome of COVID-19 is its effect on the audiovestibular system [7,8].
…”
mentioning
confidence: 99%
“…8 During the pre-vaccination clinical trials, auditory complications were not reported as a side effect. 9 Shortly after vaccination, auditory side effects, including sudden sensorineural hearing loss (SSNHL), tinnitus, earache and/or exacerbation of Menière's, and autoimmune inner ear disease, were reported in the vaccine adverse events reporting system established by the Centers for Disease Control and Prevention and FDA in the United States. 7,10,11 SSNHL is a hearing loss of ⩾30 dB at three consecutive frequencies developing within 72 h, usually due to idiopathic causes.…”
Section: Introductionmentioning
confidence: 99%